Blackwell's five-minute veterinary consult. - Graham, Jennifer E. (Jennifer Erin), 1974- (Five minute veterinary consult., 2016)
Blackwell's Five-Minute Veterinary Consult: Avian presents complete information on diseases and conditions seen in birds in a quick-reference format ideal for clinical practice. - Offers fast access to essential information on 128 avian diseases and syndromes- Written by leading experts in avian medicine- Uses the trusted Five-Minute Veterinary Consult format- Focuses on practical clinical knowledge- Includes access to a companion website offering algorithms, procedure guides, and client education handouts to download, edit, and use in practice.